PENGARUH PERLUASAN MERK TERHADAP CITRA MERK PADA PRODUK-PRODUK PEPSODENT - AULIA DANIBRATA (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2008)
The purpose of this research is to examine the influence of brand extension to the brand image. The research is motivated by the fact that product facing few failures in applying brand extension. Exogenous variable in the research is brand extension with similarity, reputation, perceived risk and innovation as the dimensions. Endogen variable in this research is brand image with knowledge and fit to the brand as the dimensions. Data consist of primary data that taken from questionnaires distributed directly to respondents. Data are collected from one hundred respondents that the consumer and user of the product. Data were tested using Structural Equation Modelling (SEM). The result of the research showed that brand extension has significant influence toward brand image.